Qualitative assessment of self-identity in people with advanced dementia. (September 2016) - Batra, Sadhvi; Sullivan, Jacqueline; Williams, Beverly R; Geldmacher, David S
This study aimed to understand the preserved elements of self-identity in persons with moderate to severe dementia attributable to Alzheimer's disease. A semi-structured interview was developed to explore the narrative self among residents with dementia in a residential care facility, and residents without dementia in an independent living setting. The interviews were transcribed verbatim from audio recordings and analyzed for common themes, while being sensitive to possible differences between the groups. The participants with dementia showed evidence of self-reference even though losses in explicit memory were evident. The most noticeable difference between the two groups was time frame reference. Nonetheless, all participants showed understanding of their role in relationships and exhibited concrete preferences. Our findings suggest that memory loss and other cognitive deficits associated with moderate to severe dementia do not necessarily lead to a loss of "self."